GBIF Occurrence Download - Occdownload Gbif.Org (The Global Biodiversity Information Facility, 2016)
A dataset containing 157878 species occurrences available in GBIF matching the query: TaxonKey: Plantae Country: Benin. The dataset includes 157878 records from 70 constituent datasets: 1348 records from Inventory of Wari maro forest (Benin). 77 records from Marie-Victorin Herbarium (MT) - Plantes vasculaires. 4 records from Phanerogamic Botanical Collections (S). 1201 records from Ecology, structure and dynamics of private plantations of Teak (Tectona grandis Lf) of the Department of the Atlantic (South Benin), 2011. 10355 records from Census of the flora of Benin. 812 records from Census of secondary forest of Itchèdè-Toffo (Southern Benin). 20850 records from Naturalis Biodiversity Center (NL) - Botany. 1339 records from Inventory of Bassila, Pénéssoulou, Wari maro, Djigbé, Lama and Bonou forests (Benin). 13 records from PRECIS. 2402 records from Census of plant species in Bonou forest reserve (Southern Benin). 12889 records from Herbier du Bénin. 127 records from Inventory of Bonou, Kilibo and Lama forests (South and centre Benin). 1127 records from Census of the secondary forests of the Lama forest reserve (Southern Benin). 162 records from Australia's Virtual Herbarium. 1 records from iNaturalist Research-grade Observations. 114 records from NMNH occurrence DwC-A. 30 records from Geneva Herbarium – De Candolle's Prodromus (G-DC). 798 records from Census of plant and animal species in sacred forests of RAMSAR sites 1017 and 1018 in Benin. 1 records from Bryophyte herbarium, Trondheim (TRH). 3 records from Continuous Plankton Recorder Dataset (SAHFOS). 2421 records from Census of plant species in Toffo forest reserve. 422 records from West-, Central- and East African Plants Databases. 3161 records from Census in Agrimey forest reserve (southern Benin). 377 records from Inventory of Niaouli forest (South-Benin). 113 records from Tropicos Specimen Data. 23 records from Natural History Museum (London) Collection Specimens. 2 records from Natural History Museum, Vienna - Herbarium W. 569 records from Spatial repartition of Antiaris toxicaria Lesch., Ceiba pentandra (L) Gaert, Terminalia superba Engl. & Diels and Triplochyton scleroxylon K. Schum. in Niaouli, Bonou, Pobe forests (South-Benin). 1 records from Karl Franzens University of Graz, Insitute for Botany - Herbarium GZU. 5422 records from West African Vegetation Database. 390 records from Inventory of Penessoulou forest (North West Benin). 532 records from Inventory of Bonou and Itchèdè forests in south east of Benin. 29 records from Royal Museum of Central Africa - Metafro-Infosys - Prelude. 5 records from Real Jardín Botánico (Madrid), Vascular Plant Herbarium (MA). 4 records from Continuous Plankton Recorder database. 15 records from Herbarium Berolinense. 659 records from United States National Plant Germplasm System Collection. 1382 records from The System-wide Information Network for Genetic Resources (SINGER). 27 records from EURISCO, The European Genetic Resources Search Catalogue. 1 records from Herbarium of Namur. 3 records from Mosses (S). 3 records from MBML-Herbario - Herbário Mello Leitão. 2603 records from Herbarium Senckenbergianum (FR). 240 records from SINGER Coordinator. 45 records from University of Ghana - Ghana Herbarium. 5422 records from West African Vegetation Database. 422 records from West-, Central- and East African Plants Databases. 4508 records from Contribution à la gestion durable des forêts : Caractéristiques écologiques et structurales de la forêt naturelle d’Akpè (Lama) au Sud du Bénin.. 5953 records from Elaboration du tarif de cubage multispécifique. 607 records from Inventory of Bassila forest (North-Benin). 181 records from Inventory of natural and agroforestry stands characterized by Xylopia aethiopica (Dunal) A. Rich. (south-Benin). 64 records from Geographically tagged INSDC sequences. 606 records from The vascular plants collection (P) at the Herbarium of the Muséum national d'Histoire Naturelle (MNHN - Paris). 1 records from Bernice P. Bishop Museum. 8 records from Carnet en Ligne. 40 records from Royal Botanic Garden Edinburgh Herbarium (E). 2 records from Botany (UPS). 10907 records from Census of species recorded during phytosociological surveys in Benin. 2 records from Bryophyte herbarium, Göttingen (GOET). 52 records from Royal Botanic Gardens, Kew - Herbarium Specimens. 2408 records from Ecology, structure and dynamics of private plantations of Teck (Tectona grandis Lf) of the Department of the Atlantic (South Benin), 2011. 1 records from CZE National PGR Inventory. 498 records from Inventory Pobè forest in South East of Benin. 1699 records from Census of plant species in Monts-Kouffè regions, center Benin. 3939 records from Census of plant species in Pahou forest reserve. 42979 records from The census of national forest of Benin .. 13 records from Geneva Herbarium – General Collection (G). 1 records from CAS Botany (BOT). 5452 records from Systematic census of the private plantations of the firewood of the Benin .. 6 records from The cryptogamy collection (PC) at the Herbarium of the Muséum national d'Histoire Naturelle (MNHN - Paris).
Keywords: GBIF; biodiversity; species occurrences